(3TQM cJGH GdLZejfi aj Yde GdgjFgs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3eMehO Hf eMeO Hf YeQ GdLZejfj GdNhGQRej,J (B744 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3abO OdJ GdHQGgjf GdYbdjI hGdThGgO GdfbdjI Ydi Cf BbUi eG jJhNi ddEfSGf ef eYGQL GdceGdGJ s
(3BNQgG (B:s
(3hgPg GdSfg fGbUI Yf GdTeSjg GdMbjbjg HYTQg CjGe hYTQjf SGYg hfUa SGYg HGdJbQjH s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B216 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B69 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3gjFI (B96) s
Keywords: (3Gdadcs